Harmonic scalpel versus other techniques for tonsillectomy: a systematic review and meta-analysis - Yi Wong, Daniel Jun; Paddle, Paul (Australian Journal of Otolaryngology; Vol 2 (January 2019): Australian Journal of Otolaryngology, 2019)
Background: The objective of this review was to compare treatment effects of harmonic scalpel tonsillectomy versus alternative techniques on postoperative pain. Secondary outcomes included delayed bleeding and intraoperative blood loss. Methods: Medline, Embase, and Central were searched for randomized controlled trials where harmonic tonsillectomy was compared to any alternative technique for participants of any age undergoing tonsillectomy. The primary outcome was pain scores using validated pain scores on day 1, day 4, and day 7 postoperatively. Data for postoperative pain scores were synthesized using random effects model and presented as standard mean difference (SMD). All outcomes were presented with 95% confidence intervals (CI). Subgroup analyses were performed based on hot or cold techniques. Results: Eleven trials were identified in this review. Five trials (637 patients) contained data that permitted meta-analysis for postoperative pain. Harmonic scalpel tonsillectomy was associated with less postoperative pain compared to other hot techniques on day 1, 4, and 7 (P